ANALYSIS OF THE IMPLEMENTATION OF DIGITAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Malika Abdujaparovna Abdurakhmanova (Modern American Journals, 2025)
This study analyzes the use of digital technologies and e-learning platforms in the educational process. It examines the opportunities provided by digital resources in modern education, the types of electronic learning systems, their advantages and disadvantages, and the conditions for their effective implementation. Based on international and national practices, relevant proposals and recommendations are developed. This thesis analyzes the practices of using digital technologies in the educational process. Based on global and local experience, it examines the effectiveness of digital tools in the classroom, their impact on students and teachers, and the conditions for successful implementation. The results of the analysis present practical suggestions for organizing digital education more effectively.
Keywords: Digital education, innovation, information technologies, analysis, digital competencies, e-learning platform, distance learning, ICT, online teaching.